The Impact of Employer Brand Equity Elements on Consumer Attitude to Service Brand - Ščiukauskė, Indrė (Vilnius University Open Series, 2021)
Increasing competition means that organisations are looking for new ways to ensure the equity of their brands, and due to the specifics of services, employees are undoubtedly one of the most important links in service brand equity creation, therefore consumer knowledge of employer brand and its equity elements can contribute to the perception towards it, change it and influence behavioural intentions. According to the theory of reasoned behaviour, attitude is an important determinant of behaviour, so the purpose of this article is to assess how elements of an employer’s brand equity influence attitude toward a service brand. After the exploratory factor analysis, 3 main elements of the employer’s brand equity were identified. An analysis of the empirical study also found that the employer brand image has the strongest effect on attitudes towards a service brand, while the effect of employer brand awareness and reputation has a weaker effect.
Keywords: employer brand; employer brand equity; impact; attitude; consumer perspective